2011
DOI: 10.4049/jimmunol.1002324
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Recruitment and Activation of Macrophages by Anti-Gal/α-Gal Liposome Interaction Accelerates Wound Healing

Abstract: Macrophages are pivotal in promoting wound healing. We hypothesized that topical application of liposomes with glycolipids that carry Gala1-3Galb1-4GlcNAc-R epitopes (α-gal liposomes) on wounds may accelerate the healing process by rapid recruitment and activation of macrophages in wounds. Immune complexes of the natural anti-Gal Ab (constituting ~1% of Ig in humans) bound to its ligand, the α-gal epitope on α-gal liposomes would induce local activation of complement and generation of complement chemotactic fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
194
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(199 citation statements)
references
References 52 publications
4
194
0
1
Order By: Relevance
“…Although no study has evaluated IB4 activity after a gastrointestinal anastomosis, we observed that IB4+ cells, which are consistent with infiltrating macrophages, were frequently present in the region of the gastrointestinal anastomosis in both tested groups. Although some authors claim that alpha‐D‐galactose epitopes on macrophage surfaces accelerate recruitment and promote wound repair 26, we were unable to verify this effect in our model, as there was no significant difference in the number of IB4+ cells in the GE group after treatment with surfactant. Therefore, additional studies are needed to determine the effect of surfactant on the recruitment and activation of macrophages in gastrointestinal anastomotic regions.…”
Section: Discussionmentioning
confidence: 56%
“…Although no study has evaluated IB4 activity after a gastrointestinal anastomosis, we observed that IB4+ cells, which are consistent with infiltrating macrophages, were frequently present in the region of the gastrointestinal anastomosis in both tested groups. Although some authors claim that alpha‐D‐galactose epitopes on macrophage surfaces accelerate recruitment and promote wound repair 26, we were unable to verify this effect in our model, as there was no significant difference in the number of IB4+ cells in the GE group after treatment with surfactant. Therefore, additional studies are needed to determine the effect of surfactant on the recruitment and activation of macrophages in gastrointestinal anastomotic regions.…”
Section: Discussionmentioning
confidence: 56%
“…These are submicroscopic !-gal liposomes comprised of glycolipids with multiple !-gal epitopes (!-gal glycolipids), phospholipids and cholesterol [18,19] (Fig. 1).…”
Section: The Natural Anti-gal Antibody !-Gal Epi-topes and !-Gal Nanmentioning
confidence: 97%
“…1). Since !-gal glycolipids comprise most of the glycolipids in rabbit red blood cell (RBC) membranes and since these cell membranes are the richest source of !-gal glycolipids in mammals [20][21][22][23], rabbit RBC are a convenient natural source for preparation of !-gal liposomes and !-gal nanoparticles [18,19,24]. For this purpose, glycolipids, phospholipids and cholesterol are extracted from rabbit RBC membranes in a solution of chloroform and methanol [25].…”
Section: The Natural Anti-gal Antibody !-Gal Epi-topes and !-Gal Nanmentioning
confidence: 99%
See 2 more Smart Citations